Pemodelan Data Konsumsi Listrik melalui Sistem IntelligEnSia Smart-meter - Pinrolinvic D.K Manembu; Angreine Kewo; Ryan L. Singgeta (Jurnal Teknik Elektro dan Komputer, 2021)
Modeling of Electricity Consumption Using IntelligEnSia Smart-meter SystemAbstract - The improvement of the Indonesian economy, which is marked by an increase in the number of people with middle and upper social economy, requires the availability of higher quality energy services. IntelligEnSia as a smart meter technology is the answer to the need for better technology services. IntelligEnSia is a smart meter technology that is able to control and monitor electricity consumption in near real time, in 30 second intervals. IntelligEnSia is able to predict electricity consumption based on available historical data patterns. Data modeling based on seasonal data descriptions, through the DSVI and MSVI approaches, is a simple technique, but is able to provide a clear understanding of electricity consumption patterns in a certain time period. The MSVI approach in the Jakarta city data case study is able to identify the relationship between independent factors such as temperature, hotel occupancy rates and rainy days with the dependent factor, namely electricity demand. This data modeling technique is able to complement the IntelligEnSia smart meter technology in answering the needs of modern society, which has previously been developed with control, monitor, prediction and missing data solution.Â Abstrak â€” Peningkatan ekonomi Indonesia yang ditandai dengan peningkatan jumlah masyarakat yang memiliki ekonomi sosial menengah keatas, membutuhkan ketersediaan layanan energi yang lebih berkualitas. IntelligEnSia sebagai teknologi smart meter menjadi jawaban akan kebutuhan layanan teknologi yang lebih baik. IntelligEnSia merupakan teknologi smart meter yang mampu mengontrol dan memonitor konsumsi listrik secara near real time, dalam interval 30 detik. IntelligEnSia mampu melakukan prediksi konsumsi listrik berdasarkan pola data historikal yang tersedia. Pemodelan data berdasarkan deskripsi data seasonal, melalui pendekatan DSVI dan MSVI, merupakan teknik sederhana, tetapi mampu memberikan pemahaman yang jelas pola konsumsi listrik dalam suatu periode waktu tertentu. Pendekatan MSVI pada studi kasus data kota Jakarta, mampu mengidentifikasikan relasi antara faktor-faktor independen seperti temperature, tingkat hunian hotel dan hari hujan dengan faktor dependen yaitu kebutuhan listrik. Teknik pemodelan data ini mampu melengkapi teknologi smart meter IntelligEnSia dalam menjawab kebutuhan masyarakat modern, yang sebelumnya telah dikembangkan dengan fungsi kontrol, monitor, prediksi dan missing data solution.